Large Effects of Small Cues: Priming Selfish Economic Decisions - Avichai Snir; Dudi Levy; Dian Wang; Haipeng (Allan) Chen; Daniel Levy (Journal of Economic Behavior & Organization (Forthcoming), 2026)
We use survey experiments to demonstrate that manipulating participants' perceptions of the context can affect their decisions. We ran three survey experiments in the U.S. and Israel with participants from both economics and non-economics majors. In the experiments, participants face a tradeoff between profit maximization (market norm) and workers' welfare (social norm). Our experimental setup enables us to discriminate between the self-selection and indoctrination effects. Existing studies find that economics and noneconomics students make different choices in such situations, which the studies argue is because of differences in personality traits between economics students and others. While such differences might exist, we argue that context also plays an important role. Using priming to manipulate the context, we demonstrate that when participants receive cues signaling that their decision has an economic context, both economics and non-economics students tend to maximize profits. When participants receive cues emphasizing social norms, on the other hand, both economics and non-economics students are less likely to maximize profits. We find that the role of context in determining behavior is at least as large as the baseline differences between economics and non-economics students.
Keywords: A11; A12; A13; A20; B40; C90; C91; D01; D63; D91; P10; 330; Behavioral Economics; Experimental Economics; Market Norms; Social Norms; Self-Selection; Indoctrination; Self-Interest; Economic Man; Homo Economicus; Rational Choice; Fairness; Laboratory Experiments; Priming; Economists vs Non-Economists